2019
DOI: 10.5644/ama2006-124.272
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Bilateral Duplication of the Suprascapular Vein and Its Relation to the Superior Transverse Scapular Ligament Revealed by Anatomage Table

Abstract: Objective. The aim of our paper is to present a rare variation of the suprascapular vein, its incidence and clinical significance. Case Report. A rare case of a double suprascapular vein was observed in a digitalized human cadaver on Anatomage Table 5.0. The vein divided into two branches, one passing over the transverse scapular ligament, while the other one coursed underneath the ligament, inside the notch. Conclusion. This variation has major clinical importance as it is associated with the appearance of Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The SSV could be absent or duplicated ,but its drainage generally was to the EJV. [15,16] In the present case, its drainage was into the jugulo-subclavian venous confluence.…”
Section: Discussionmentioning
confidence: 52%
“…The SSV could be absent or duplicated ,but its drainage generally was to the EJV. [15,16] In the present case, its drainage was into the jugulo-subclavian venous confluence.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, Panagouli and co-workers [ 19 ] demonstrated that the Asian female cadaver with gastric cancer has an unusual bilateral duplication of the suprascapular vein, which, usually crossing the back triangle of the neck, enters in the external jugular vein [ 39 ], and it is accompanied, along its course, by the suprascapular artery. Both blood vessels are localized over superior transverse scapular ligaments which form a foramen, in which pass the supravascular nerve.…”
Section: Resultsmentioning
confidence: 99%
“…The Asian female cadaver shows two supravascular vein branches which drain in the subclavian vein. One branch is localized together with the scapular artery over the scapular ligaments; the other one passes under the same ligaments, accompanied by the supravascular nerve [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the case presented by Panagouli et al (1) concerning the unusual bilateral duplication of the suprascapular vein revealed by the Anatomage table. It is valuable to report findings on the cadavers incorporated into the Anatomage table because this resource is accessible worldwide.…”
mentioning
confidence: 97%